Achieving Supply Chain Excellence through Effective Supplier Management: A Case Study of a Marine Organisation - Nurul Syakirah Mohd Zailan; Premkumar Rajagopal; Veera Pandiyan Kaliani Sundram; Raja Zuraidah Rasi; Nor Ratna Masrom; Zamry Gafar (International Journal of Supply Chain Management, 2020)
The researcher in this study attempted to understand the efficiency of the suppliers on supplied products in a marine company in Malaysia. The paper seeks to find out how supplier management leads to supply chain excellence. Also, the paper attempts to capture the buyer-supplier relationship and management of its supply performance. The research design for this study is a qualitative method by using interviews that are conducted for respondents from the Purchasing Department. This research used a single case study in JM Marine Pvt Ltd. The samples are consists of 5 respondents to examine the research model. First, content analysis of the interview was derived to understand the management of the supplier in purchasing the products for vessels. Supplier delivery performance, quality products, and reliability were found to be the most crucial criteria for choosing the supplier. Second, supplier selection and supplier evaluation were found to be a major of supplier efficiency to perform a good supply chain. The result of this study will give ideas to the practitioners and encourage organizations to give more emphasizes on supplier selection and supplier evaluation to achieve supply chain excellence.